Evaluation and Comparison of Plasma miRNA-31 in Oral Squamous Cell Carcinoma - Caliaperoumal, Santhosh Kumar; Ravi, Saranyan; Thirumaran, M.; Jeyakumar, Balakrishnan; Mani, Devi (International Journal of Statistics in Medical Research, 2022)
Background/Purpose: Oral Squamous cell carcinoma is sixth most common cancer with considerable morbidity and mortality. The microRNAs (miRNAs) are set of short RNAs involved in regulating the expression of protein coding genes. They are up or down-regulated in carcinogenesis and in oral cancer. The miRNA-31 (miR-31) is increased in oral cancer. Objective: To evaluate and compare the expression of miRNA-31 in plasma of Oral squamous cell carcinoma and control subjects. Materials and Methods: Case control study was carried out in 25 cases of oral squamous cell carcinoma subjects and 25 normal control subjects. The level of miRNA-31 in blood plasma was evaluated by miRNA easy kit (quagen) and miRNA-based qRT-PCR. The fold change was observed and compared between OSCC and controls. Results: The plasma level of miRNA-31 was significantly increased in OSCC patients compared to controls (p<0.001). The patients with moderately differentiated, grade 4 OSCC patients showed significant increase in fold change compared to control, well differentiated and grade 3 OSCC (p<0.001). Conclusion: Our results indicate that plasma miR-31 may be used as an adjuvant biomarker the detection of OSCC patient.